Manajemen Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Publik di Desa Sepapan Kecamatan Jerowaru Kabupaten Lombok Timur - Ardi Wiranta; Andika Wahyu Rendi; Abdurrahim (Pendidikan Al-Gafari, 2024)
Public service is an activity carried out by a person, group, or certain agency to provide services to the community to facilitate a process of achieving certain goals, both from a social, political, and economic perspective. This research was conducted with the aims: 1) To find out the Village government's planning in improving the quality of public services in Sepapan Village, Jerowaru District, East Lombok Regency, 2) To find out the organization of the village government in improving the quality of public services in Sepapan Village, Jerowaru District, East Lombok Regency, 3) To find out how the village head supervises in improving the quality of public services in Sepapan Village, Jerowaru District, East Lombok Regency, and 4) To find out the form of BPD supervision of village heads in improving the quality of public services in Sepapan Village, Jerowaru District, East Lombok Regency. This type of research is descriptive qualitative research. Data collection techniques use observation, interviews, and documentation methods. The subjects of this research were the village head, village staff, and the Sepapan village community. The results of this research indicate that public service management in Sepapan village, Jerowaru subdistrict can be said to be good, this is strengthened by the findings made by researchers during field observations, and the completeness of data in providing public services.